2020
DOI: 10.5430/ijfr.v11n3p31
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Accounting Adoption Barriers Among Malaysian Hotel Companies

Abstract: Environmental management has become a main concern to the hotel industry with regards to waste reduction, energy savings and water conservation. The hotel industry is frequently accompanied by many adverse environmental impacts as hotel companies extensively consume large amounts of energy, water and non-durable products. Environmental Management Accounting (EMA) is tools that can be used to assist these companies to trace, collect, and analyse physical and monetary environmental information for decision-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Through EMAS adoption, both financial and non-financial environmental-related information are identified, collected, and used for the strategic business plan within the organization. However, prior research also found that the adoption of both Physical Environmental Management Accounting (PEMA) and Monetary Environmental Management Accounting (MEMA) was below the midpoint level (Ahmad et al, 2020;Mat Yusoh & Tuan Mat, 2020;Phan et al, 2017). Furthermore, environmental accounting practice in the service industry is weaker when compared to other sectors, and that most companies still insufficiently use environmental management to reduce their environmental footprint (Jankovic & Krivacic, 2014).…”
Section: Emas Adoption In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations
“…Through EMAS adoption, both financial and non-financial environmental-related information are identified, collected, and used for the strategic business plan within the organization. However, prior research also found that the adoption of both Physical Environmental Management Accounting (PEMA) and Monetary Environmental Management Accounting (MEMA) was below the midpoint level (Ahmad et al, 2020;Mat Yusoh & Tuan Mat, 2020;Phan et al, 2017). Furthermore, environmental accounting practice in the service industry is weaker when compared to other sectors, and that most companies still insufficiently use environmental management to reduce their environmental footprint (Jankovic & Krivacic, 2014).…”
Section: Emas Adoption In Malaysiamentioning
confidence: 99%
“…Prior research found that the adoption level of EMAS in Malaysia is still at the infancy stage (Ahmad et al, 2020;Mat Yusoh & Tuan Mat, 2020). Research by Jamil et al (2015) that focuses on small-medium manufacturing companies shows that EMAS adoption in Malaysia is still low due to a lack of institutional pressures.…”
Section: Level Of Emas Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, enhancing global sustainability among SMEs and communities calls for the introduction of policies and the development of methodologies [18], among which is the adoption of green environmental management accounting system (EMAS) [19]. EMAS is essentially an instrument that facilitates environmental performance management in firms and environmental information reporting to all stakeholders (internal and external) [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to Asiaei et al [1], the decision of a firm to manage its environmental impact would involve the integration of accounting data and environmental data and strategies, and, to this end, EMAS has been known to achieve high corporate environmental performance. The objective of these firms is competitive advantage sustainability through the adoption of an environmental approach; for instance, the efficiency of firms can be enhanced through the elimination of contamination from manufacturing processes (via minimal required input, short processes, and control of compliance-related expenses and accountabilities) [18]. To this end, literature has documented the increasing momentum of environmental accounting among firms in search of sustainability [21][22][23].…”
Section: Introductionmentioning
confidence: 99%